2012
DOI: 10.1007/s11356-012-0881-5
|View full text |Cite
|
Sign up to set email alerts
|

Daily, seasonal and monthly variations in ozone levels recorded at the Turia river basin in Valencia (Eastern Spain)

Abstract: Results show a different behaviour of the monthly means and the daily cycles depending on the season of the year and the measuring environment, with summer/winter ratios ranging from 2.4 in cities to 1.6 inland, and mean values always higher in the interior of the basin. Daily cycles show significant summer/winter differences related to the predominant situations of anticyclonic stability in winter, which limit ventilation, and the predominant breeze circulations in summer. Results also show a "weekend effect"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…26 In addition to local sources, ozone precursors (NO x , volatile organic compounds (VOCs)) can also be transported over long distances from the source and cause ozone formation in the downwind locations. 27 The balance between local and long-range transport effects are assumed to depend strongly on regional meteorological and geographical differences. The representation of chemistry and accurate ozone precursor emission inventories in the model is very important to reproduce O 3 globally and regionally.…”
Section: Introductionmentioning
confidence: 99%
“…26 In addition to local sources, ozone precursors (NO x , volatile organic compounds (VOCs)) can also be transported over long distances from the source and cause ozone formation in the downwind locations. 27 The balance between local and long-range transport effects are assumed to depend strongly on regional meteorological and geographical differences. The representation of chemistry and accurate ozone precursor emission inventories in the model is very important to reproduce O 3 globally and regionally.…”
Section: Introductionmentioning
confidence: 99%
“…They studied different time windows and obtained daily predictions with accuracy and robustness. Castell-Balaguer et al [15] applied descriptive methods to analyze the seasonal variations of O 3 in the Turia river basin, including two of these urban sites. They concluded that the average daily and monthly dynamics had summer/winter differences, depending on the location.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 gives the characteristics of these sites. The Mediterranean Centre for Environmental Studies Foundation applied quality control methods to the data set used in this work [16]. The report [17] assessed air pollution health impacts in Valencia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganor et al () relate the occurrence of mineral dust outbreaks in the Eastern Mediterranean to the presence of thermal low‐pressure areas over Maghreb. In the Iberian Peninsula ( IP ) under anticyclonic conditions, mesoscale phenomena control O 3 during summer along the Spanish Mediterranean coast (Millán et al , ; Barros et al , ; Gonçalves et al , ; Castell‐Balaguer et al , ). In summer, under a blocking anticyclone over Central Europe, there is a net transport of O 3 and precursors towards NW Spain that increases surface O 3 concentration (Saavedra et al , ).…”
Section: Introductionmentioning
confidence: 99%